2020
DOI: 10.1177/0361198120962801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Uncertainty and Social Networks on Shadow Evacuation and Non-Compliance Behavior in Hurricanes

Abstract: Shadow evacuation and non-compliance are among undesirable behaviors during hurricane events. Based on a post-Hurricane Matthew household survey, this study aims to understand the combined effects of information source and uncertainty on individual-level evacuate–stay decisions from the Jacksonville, Florida metropolitan area. A random parameter logit model is developed to capture the heterogeneous effects among individuals. The combined effects are substantial and distinct in the two cases and the study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…2016; Gagné 2020; Ling et al. 2020); this pattern of additional psychological distress has been reported under stay‐at‐home orders (Williams et al. 2020).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…2016; Gagné 2020; Ling et al. 2020); this pattern of additional psychological distress has been reported under stay‐at‐home orders (Williams et al. 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Not only does social context shape the degree to which citizens learn about and respond to government calls for crisis preparation, but reactions to government action following the crisis are contingent on both social context and the actions of government (Arceneaux and Stein 2006;Chamlee-Wright and Storr 2010;Gasper and Reeves 2011). Both crowding and isolation are expected to affect compliance and reactions, with those with larger networks generally seeming to comply more with government orders to evacuate and having fewer negative psychological stressors following a disaster compared to isolates (Bryant et al 2016;Gagné 2020;Ling et al 2020); this pattern of additional psychological distress has been reported under stay-at-home orders (Williams et al 2020). At the same time, larger households are less likely to comply with orders to evacuate around natural disasters, and crowding is correlated with higher stress responses following a disaster (Dash and Hearn Morrow 2000;Kawano et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of the random coefficients for order issuance reveals household heterogeneity in responding to evacuation orders (i.e., order compliance and the presence of shadow evacuation). Ling et al [29] further distinguished those who received an evacuation order from those who did not with data from Hurricane Matthew (2016). Two separate random parameter logit models were estimated to understand order-compliance behavior and shadow evacuation, respectively.…”
Section: Current Practices and Studies Of Phased Evacuationmentioning
confidence: 99%